Characterization of Erysipelothrix rhusiopathiae Isolates from Diseased Pigs in 15 Chinese Provinces from 2012 to 2018 - Chao Wu; Changjie Lv; Ya Zhao; Weifeng Zhu; Liang Liu; Ting Wang; Chao Kang; Ying Yang; Xiaomei Sun; Qiang Zhang; Meilin Jin (Microorganisms, 2021)
Erysipelothrix rhusiopathiae can cause erysipelas in animals and erysipeloid in humans. Since its recurrence in 2012, swine erysipelas has caused serious losses within the pig industry in China. The aim of this study was to perform multilocus sequence typing and understand the virulence and antimicrobial susceptibility of E. rhusiopathiae isolates in China. Multilocus sequence typing (MLST) of a total of 120 strains was performed, and as a result, three different sequence types were identified, of which ST48 was the main one. Five isolates of each MLST type were randomly selected to be used to challenge mice. ST48 was associated with a higher virulence. Antimicrobial susceptibility was tested using a microdilution technique and, to analyze the resistance mechanism, six strains were selected for genome sequencing. A comparison of the six genomes indicated the presence of a suspected macrolide resistance gene, namely, Erm(A)-like, in erythromycin-resistant strains, which increased the minimum inhibitory concentration (MIC) of erythromycin against E. coli C600 at least four-fold. In addition, three mutations (gyrA86T-I, gyrA90D-N, and parC81S-I) were observed in the quinolone resistance-determining regions (QRDRs) of gyrA and parC in quinolone-resistant strains. After the gyrA gene with the 86T-I mutation or the parC gene with the 81S-I mutation was transfected into E. coli C600, the MIC of enrofloxacin against this strain increased at least two-fold. Our findings provide a theoretical basis for developing antibacterial drugs and may contribute to the clinical prevention and control of E. rhusiopathiae.